Eosinophilic Cationic Protein in Bronchial Asthma current concepts (Bangladesh Journal of Medical Microbiology, 2013)
Bronchial asthma is a chronic and inflammatory disease of lungs.  On the basis of pathogenesis, asthma can be grouped into allergic, inflammatory, neurogenic and physical mechanisms.  It is characterized by a 50 fold increase in the number of eosinophil in relation to neutrophil in the bronchial mucosa. After allergic sensitization, regulatory Th2 cell releases IL-5.  This IL-5 is responsible for differentiation and maturation of eosinophil. On re-exposure, activation and degranulation of eosinophil occur. In this review this mechanism is described in updated way.DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19331 Bangladesh J Med Microbiol 2013; 07(02): 25-27